Enhancement of Heterogeneous Ethyl Oleate Synthesis Using Aqueous Ethanol - Mohd Sabri, Mahmud; Safinski, Tomasz; Nelson, Mark Ian; Adesina, Adesoji Adediran (AENSI Publishing, 2017)
Biodiesel synthesis using heterogenous catalyst usually results in compromise rate of reaction due to mass transfer limitation during the reaction. An alternative is reported in this paper to produce biodiesel from free fatty acids in a liquid-liquid system using immobilized lipase. The yield of reversible reactions, which is naturally deteriorated by the presence of water because of thermodynamic limitation, nevertheless remained and the rate increased until 2 manifolds when water was initially added from 0.15 wt% to 15 wt%. The reaction tests were conducted in a batch reactor at 45oC using the feed ratio, beta (0 < beta < 2.5) and all runs were performed under free mass transport limitation. The result also shows that the increment of rates were prominent in excess oleic acid mixtures implying the enhancement of clearly discriminated liquid phase during the reaction.